CORRECTING OF ANEMIA USING IRON SUCROSE IN PATIENTS WITH CHRONIC KIDNEYDISEASE STAGE VD ON HEMODIALYSIS - Dudar, I.; Shifris, I.; Gonchar, Y.; Savchuk, V.; Loboda, O.; Krasyuk, E.; Aleksieva, N. (Ukrainian Journal of Nephrology and Dialysis, 2014)
Anemia is a common complication of CKD. Iron deficiency is one of a leading cause of anemia in HD patients. The causes of iron deficiency in these patients are multifactorial. Main factors that contribute to iron deficiency in HD patients are reduction intake and impaired intestinal absorption of dietary iron, blood losses, chronic inflammation and increased iron requirements during therapy with erythropoiesis–stimulating agents. Aim.The aim was to study efficacy and safety of iron sucrose (Venofer) in HD patients with anemia. Materials and methods. This study was an retrospective, epidemiologic, performed from 2010 to 2014 years. The study included 69 HD patients with anemia from dialysis single–center. 38 (55.1%) patients were men, average age 49,53 ± 3,9years and the most common cause of ESRD was glomerulonephritis (37 patients, 53.6%). Hemoglobin value was analyzed weekly. The levels of serum ferritin and transferrin saturation, were determined before and after treatment with Venofer. Results. Treatment with the Venofer resulted a significant increase of hematological and iron exchange parameters. At 2 – 3 weeks of therapy, hemoglobin levels increased by 7,6% and 10,7%, respectively. 14 days after the last dose Venoer serum ferritin and transferrin saturation levels have increased by 58% and 55%, respectively. Conclusions. Intravenous iron is the preferred route of administration in HD patients. Venofer showing a significant increase both of hemoglobin and iron exchange markers levels on a background of insignificant frequency of treatment–related adverse events.